The Role of Big Data in Crime Prevention and Criminal Law Enforcement: Balancing Efficiency and Personal Data Protection - Sihotang, Lesson; July Esther; Sinaga, Jusnizar; Siahaan, Yanti Tiara Br; Ndruru, Donius (Universitas Negeri Semarang, 2025)
Crime prevention and criminal law enforcement require clear arrangements so that at the same time they can form good protection for every Indonesian citizen's personal data. The purpose of this paper is to analyse the concept of using big data in crime prevention as well as criminal law enforcement and the form of boundaries and protection of personal data in the use of big data in crime prevention as well as criminal law enforcement. To achieve the results used, the research method used is a case approach and a statutory approach. From this writing, the use of big data in the context of crime prevention and criminal law enforcement has grown rapidly along with IT advances. Big data includes the collection, analysis and processing of large and diverse amounts of information. In disclosing crime cases using big data, it must also be linked to regulations on personal data protection and the data used in case disclosure must also be guaranteed validity, so that the activities carried out do not damage the sense of justice in society